GENDER EQUALITY IN FAMILY LAW IN MOROCCO - Ijtihadul Umam; Luq Yana Chaerunnisa (Institut Agama Islam Ngawi, 2023)
Abstract: Inequality has arisen as a result of the emergence of gender issues in Morocco, produces inequality that causes injustice to women, including marginalization, subordination and domestic violence. It is essential to advocate for the reform of gender-biased legal regulations. The purpose is to discuss Moroccan family law reform and the importance of gender equality. Descriptive qualitative analytic research is the type of study in question. Books, articles, institutional reports, and other written and digital sources were used to gather the data. According to the study's findings, Family Law Reform in Morocco has brought about a level of regulation in people's lives that helps them achieve equal rights and opportunities. The Maliki School, which focuses on Maslahah Mursalah's content, aims to internalize the legal principles outlined in Family Law in Morocco. Gender equality is reflected in the rules regarding the position of women and men in household life, such as divorce, marital conditions, questions about children's rights, and the duties and responsibilities of wives and husbands to one another. Equality practices in society, particularly in the family, have emerged as a direct result of the Family Law reform. Keywords: Gender Equality, Inequality Among Women, and Family Law Abstrak: Maraknya isu gender yang berkembang di Maroko menghasilkan ketimpangan yang menyebabkan ketidakadilan pada perempuan, di antaranya marginalisasi, subordinasi serta kekerasan dalam rumah tangga. Hal itu menjadi penting untuk menyuarakan pembaruan aturan hukum yang dinilai bias gender. Tujuan penelitian yakni menjelaskan pembaruan hukum keluarga di Maroko dan nilai kesetaraan gender dalam hukum keluarga di Maroko. Jenis penelitian ini yaitu kualitatif deskriptif analitik. Data dikumpulkan melalui literatur di antaranya buku, artikel, laporan lembaga baik tertulis ataupun sumber digital. Hasil telaah menunjukkan bahwa Pembaruan Hukum Keluarga di Maroko menjadi tataran peraturan di kehidupan masyarakat untuk mewujudkan persamaan hak dan kesempatan yang sama. Internalisasi nilai-nilai hukum yang terkandung pada Hukum Keluarga di Maroko ialah Mazhab Maliki, yang memperhatikan kandungan Maslahah Mursalah. Nilai kesetaraan gender terlihat di aturan-aturan tentang posisi perempuan dan laki-laki di kehidupan berumah tangga, di antaranya, mengenai tugas dan kewajiban istri dan suami antara satu dan lainnya, perceraian, kondisi pernikahan, dan pertanyaan tentang hak-hak anak. Adanya reformasi Hukum Keluarga tersebut, menjadi cikal bakal terbentuknya praktik kesetaraan di masyarakat, terutama di ranah keluarga. Kata Kunci: Ketidakadilan Perempuan, Kesetaraan Gender dan Hukum Keluarga